Respiratory muscle training improves cardiopulmonary function and exercise tolerance in subjects with subacute stroke: a randomized controlled trial - Sutbeyaz, Serap Tomruk; Koseoglu, Fusun; Inan, Levent; Coskun, Ozlem (Clinical rehabilitation, 2010)
Objective: To determine whether two types of exercise — breathing retraining (BRT) and inspiratory muscle training (IMT) — improve on cardiopulmonary functions and exercise tolerance in patients with stroke. Design: A randomized controlled trial. Setting: Education and research hospital. Subjects: Forty-five inpatients with stroke (24 men, 21 women) were recruited for the study. The subjects were randomized into three groups: 15 assigned to receive inspiratory muscle training (IMT); 15 assigned to received breathing retraining, diaphragmatic breathing and pursed-lips breathing (BRT); 15 assigned to a control group. Interventions: All study groups participated in a conventional stroke rehabilitation programme. For the same period, the IMT and BRT groups trained daily, six times a week, with each session consisting of one half-hour of training for six weeks. Main measures: Each subject underwent pulmonary function and cardiopulmonary exercise tests. Subjects were also assessed for exertional dyspnoea, stages of motor recovery, ambulation status, activity of daily living and quality of life. Results: After the training programme, the IMT group had significantly improved forced expiratory volume at 1 second (FEV1), forced vital capacity (FVC), vital capacity (VC), forced expiratory flow rate 25—75% (FEF 25—75%) and maximum voluntary ventilation (MVV) values compared with the BRT and control groups, although there were no significant differences between the BRT and control groups (P<0.01). Peak expiratory flow rate (PEF) value was increased significantly in the BTR group compared with the IMT and control groups. The IMT group also had significantly higher peak oxygen consumption (Vo2peak) than the BRT and control groups, although there were no significant differences between the BRT and control groups (P<0.001). There was a statistically significant increase in maximum inspiratory pressure (PImax) and maximum inspiratory and expiratory pressure (PEmax) in the BRT group and, PImax in the IMT group compared with baseline and the control group. In the IMT group, this was associated with improvements in exercise capacity, sensation of dyspnoea and quality of life. Conclusions: Significant short-term effects of the respiratory muscle training programme on respiratory muscle function, exercise capacity and quality of life were recorded in this study.